Efficient synthesis of xanthenedione derivatives using cesium salt of phosphotungstic acid as a heterogeneous and reusable catalyst in water. Issue 21 (1st November 2016) - Thakur, Ashima; Sharma, Alka; Sharma, Abha
ABSTRACT: Cs2.5 H0.5 PW12 O40 has been reported to be an efficient catalyst for the synthesis of 1, 8-dioxo-octahydroxanthene from aldehydes and 1, 3-cyclohexanedione/dimedone in water. This approach is environmentally benign with clean synthetic procedure, short reaction time, easy workup procedure, excellent yield, and regeneration of catalyst, which made this protocol efficient and safe. GRAPHICAL ABSTRACT: